Effect of Precursor Solution Aging on the Crystallinity and Photovoltaic Performance of Perovskite Solar Cells. Issue 11 (30th January 2017) - Tsai, Hsinhan; Nie, Wanyi; Lin, Yen‐Hao; Blancon, Jean Christophe; Tretiak, Sergei; Even, Jacky; Gupta, Gautam; Ajayan, Pulickel M.; Mohite, Aditya D.
Abstract : Perovskite materials due to their exceptional photophysical properties are beginning to dominate the field of thin‐film optoelectronic devices. However, one of the primary challenges is the processing‐dependent variability in the properties, thus making it imperative to understand the origin of such variations. Here, it is discovered that the precursor solution aging time before it is cast into a thin film, is a subtle but a very important factor that dramatically affects the overall thin‐film formation and crystallinity and therein factors such as grain growth, phase purity, surface uniformity, trap state density, and overall solar cell performance. It is shown that progressive aging of the precursor promotes efficient formation of larger seeds after the fast nucleation of a large density of small seeds. The hot‐casting method then leads to the growth of large grains in uniform thin‐films with excellent crystallinity validated using scanning microscopy images and X‐ray diffraction patterns. The high‐quality films cast from aged solution is ideal for thin‐film photovoltaic device fabrication with reduced shunt current and good charge transport. This observation is a significant step toward achieving highly crystalline thin‐films with reliability in device performance and establishes the subtle but dramatic effect of solution aging before fabricating perovskite thin‐films. Abstract : A direct correlation between precursor aging time and crystalline quality of hybrid perovskite‐based thin films is discovered and systematically elucidated. Progressive aging of precursor results in a pinhole‐free thin film with optimal phase purity that results in high‐efficiency planar solar cells.